Exploring the Changing Contours of "Enchantment" - George, Jibu Mathew (2021)
By the phrase "disenchantment of the world" (Entzauberung der Welt), Max Weber meant: i) an understanding of the world increasingly by reference to natural forces, physical laws, and mechanical principles than to magical and supernatural powers; and ii) a development within religion from magic to rationalized paths to salvation devoid of magic. However, restricting exploration on enchantment, disenchantment, and re-enchantment to scholarly and historically specific meanings would exclude a large terrain of ordinary, non-religious human experience. The semantic flexibility of the terms enables one to explore a spectrum of so-called substitutive sources of re-enchantment: psyche, death, love, art, history, nature, and so on. To designate secular sources of enchantment exclusively as re-enchantments would restrict them to being substitutes to the religious. Further, not all religious imagination is enchanting; the nature of enchantment varies across the ideational spectrum of religious world views, and this article briefly examines the internal gradations. Based on its exploratory expansiveness vis-à-vis such diverse phenomena, the article argues that every object, entity, and experience is a potential source of enchantment, that enchantment and disenchantment in a larger sense have to do with the perspective one might bring to an otherwise inert world, and that enchantment occurs at the conjunction of the subject and the object.
Keywords: Death; Enchantment; Literary art; Max Weber; Naturalism; Psyche; World appetite; World comprehension; World creation; World excess